The Criticism and Study of the Morphology Chapter of "Arabic Morphology & Syntax" Book - Sayyed Mohammad Reza l Ibnorrasoo; Elahe Safian (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The first press of "Arabic Morphology & Syntax 1 - 2" - which is written by Abbas Mahyar - has been edited by "The Center for Studying and Compiling University Books in Humanities" (SAMT) in 1385 (2006) as a main book of Arabic Morphology & Syntax 1 – 2 lessons for students of Persian Literature in B.A which is considered as an eight-unit course , and it has been republished twice since then.The authors in the present paper  aimed to  analyze and criticize the Morphology chapter of this book from several viewpoints, such as the conformity of the book subjects with approved topics by Planning Higher Council, the correctness or inaccuracy of the explanation and examples given for the grammatical concepts, attention or inattention to importance, necessity, and the use of presented grammars for the students of  Persian Literature, correcting the word & phrases pronunciation in the text and exercises, as well as the typographic mistakesthat cannot be ignored.